IMPLEMENTATION OF RENEWABLE ENERGY CONCEPT IN THE AUTOMOTIVE INDUSTRY IN MALAYSIA: AN EXPLORATORY STUDY. - Salleh, NurFarahin binti; Muhsen Alhayali, Zaid Ahmed Bin; Chew, Boon Cheong; Abd. Hamid, Mohd. Syaiful Rizal bin (Journal of Technology Management and Business, 2017)
This paper discusses on the growing concern about the consequences of climate change, and the increase in the rate of natural disasters around the world, it becomes very important for the world to witness a great shift in the use of energy. Many solutions appeared to prevent the environment from climate change. This solution varies from developing new mechanisms and technologies to generate less CO2 from fossil fuel such as energy efficiency concept in automotive, cement and petrochemical industries. Shifting from oil to gas in some industries like electricity generation and renewable energy which is the main focus of this research. In Malaysia, renewable energy considers as a fifth source of energy. Different types of renewable energy have been used in various sectors. The aim of this research is to understand the level of renewable energy in Malaysia, the rules and regulations that have helped green technology to flourish in Malaysia, and finally how the automotive industry responses to the changes in the business environment to meet the challenge of climate change. Four research questions have developed to achieve the aim of this research. In designing this research two methods have implemented; focused literature review and multiple case studies to understand the beginning of the awareness towards climate change as well as the current situation of the renewable energy in Malaysia, literature review is a crucial factor to achieve the research aim. Multiple case studies will be followed in this research. To have in depth understanding of renewable energy in Malaysia, case study is important. The findings of this research suggest that Green technology in Malaysia still in the developing stage. The investment in green products is too high which needs to consider in relation with market size. Malaysian government is playing the major role in supporting green concept. in terms of the public awareness, more actions need to be taken to encourage more consumers to consider green products services and their first choice. Â